Revisiting 1956: B. R. Ambedkar and states reorganization - Pai, Sudha; Kumar, Avinash (New Delhi Orient Blackswan Private Limited, 2018)
Revisiting 1956 is a twopart volume discussing and republishing Ambedkar's writings on the reorganisation of Indian states. The first part of the volume is a monograph by the authors and besides commenting on Ambedkar's views, it also provides a historical context of his views. It also traces the evolution of Ambedkar's ideas through the early part of the 1950s and notes that the issues he discusses are very much relevant today. The second part is a compendium of Ambedkar's works that have been cited and referred to in the first part. This volume is a copublication with Indian Institute of Dalit Studies, New Delhi.
Keywords: State governments; Political and social views